In Memory of Professor Anna Pałubicka (November 15, 1947 - January 21, 2026), Editor-in-Chief of Sensus Historiae from 2015 to 2018 - Dominiak, Grzegorz A.; Bugajewski, Maciej (Sensus Historiae, 2025)
The academic community associated with the journal Sensus Historiae received the news of the passing of the distinguished scholar and philosopher, Professor Anna Pałubicka, with sadness and deep regret. From the time Sensus Historiae was first published (in 2010) until almost her final days, Professor Pałubicka supported the journal. As a member of its editorial board, she ensured its academic standards, and as a reviewer of articles published in the quarterly, she contributed to their substantive quality. Finally, when she served as Editor-in-Chief of Sensus Historiae from 2015 to 2018, she not only ensured the journal’s scholarly content, but also upheld high ethical standards.